1987
DOI: 10.1121/1.2024881
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and gap detection with filtered and broadband noise signals

Abstract: The higher audiometric frequencies arguably are the most important for some tasks requiring fine temporal discriminations. Both modulation and gap detection thresholds improve with increasing center frequency of noise bands. For modulation detection, however, not all investigators are convinced that improved performance is necessarily dependent on sensitivity at the higher center frequencies. They point out that the high-frequency advantage for modulation detection may be a consequence of concomitant increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
28
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 0 publications
9
28
0
Order By: Relevance
“…However, the similarity in the shapes of our average neural TMTFs with those determined behaviourally with twice the modulation-frequency resolution (Klump and Okanoya, 1991) suggests that the lower high frequency slopes of the TMTFs in the starling may be real. The high-frequency roll-off of the TMTF determined for the starling's auditory-nerve fibres is also very similar to the high-frequency roll-off in other behavioural studies in humans (Viemeister, 1979;Forrest and Green, 1987;Formby and Muir, 1988), chinchilla (Salvi et al, 1982) and the parakeet (Dooling and Searcy, 1981).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, the similarity in the shapes of our average neural TMTFs with those determined behaviourally with twice the modulation-frequency resolution (Klump and Okanoya, 1991) suggests that the lower high frequency slopes of the TMTFs in the starling may be real. The high-frequency roll-off of the TMTF determined for the starling's auditory-nerve fibres is also very similar to the high-frequency roll-off in other behavioural studies in humans (Viemeister, 1979;Forrest and Green, 1987;Formby and Muir, 1988), chinchilla (Salvi et al, 1982) and the parakeet (Dooling and Searcy, 1981).…”
Section: Discussionsupporting
confidence: 59%
“…Typically, the temporal modulation transfer functions have a low-pass or band-pass characteristic, and the minimum integration time can be derived from the upper cut-off frequency of this function as a parameter that describes the auditory system's temporal resolution. In the auditory systems studied so far with both paradigms using psychoacoustic methods, the minimum integration time is about half the duration of the minimum-detectable gap (human: see Formby and Muir, 1988, for a review; chinchilla: see Henderson et al, 1984 andGiraudi et al, 1980; European starling: Maier, 1989, andOkanoya, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, mean threshold values for gap detection with low-pass filtered noise and cutoff or center frequencies of 1000 Hz have varied from 6.9 to 12.5 msec (Fitzgibbons, 1983;Fitzgibbons & GordonSalant, 1987;Formby & Muir, 1988;Shailer & Moore, 1983). Shailer and Moore (1985) estimated the 70.7% thresholds for gap detection by using a center frequency of 1000 Hz and five bandwidth values ranging from .0625 to 1.0 as a proportion of the center frequency.…”
mentioning
confidence: 99%
“…A brief pause in a continuous tone, however, can be regarded as an empty interval with markers of very long duration. For studying thresholds for detection of a single gap in noise, subjects are presented with gaps embedded either in auditory signals lasting for 400-500 msec (see, e.g., Florentine & Buus, 1984;Formby & Muir, 1988) or in ongoing, continuous noise (e.g., Buunen & van Valkenburg, 1979;Fitzgibbons, 1983Fitzgibbons, , 1984.…”
mentioning
confidence: 99%
“…Studies using normal-hearing listeners as subjects have shown that loss of high-frequency hearing sensitivity (via low-pass filtering or masking) alversely affects temporal acuity (Patterson et al, 1978;Florentine and Buus, 1984;Bacon and Viemeister, 1985;Formby and Muir, 1988). Listeners with high-frequency hearing losses show the deficits expected due to lack of high-frequency information (Florentine and Buus, 1984;Bacon and Viemeister, 1985); some show an additional deficity, indicating that temporal resolution oer se may be affected by the hearing loss (Florentine and Buus, 1984).…”
Section: B Audiograms Of Sonar Technicians Failing the Hearing Testmentioning
confidence: 99%